Analysis of The Views of Students At MAN 2 Jambi City on Social Media In Influencing the Learning Process in Schools - Al-fiqri, M. Rizki; Repino Putra, Ojto Disyah; Halilintar, Putra; Maryadi, Slamet; Kurniawan, Rananda Rizki; Ramadana, Randi (International Journal of Education and Teaching Zone, 2023)
This study looked at the role of social media from a student's point of view on the learning process in MAN 2 Jambi City. This type of research is descriptive qualitative. The subjects in this study were grade 12, which amounted to 34 students, whereas the sample was 18 students. The sample was taken randomly using random sampling techniques. Researchers collect data by using a Google form, which is then analyzed to see the views of MAN 2 Jambi City students on the role of social media in the learning process. The results showed that the role of social media is constructive for MAN 2 Jambi City students in the learning process.